Tsad maʼi bstan bchos chen po rigs rgyan = Seven treatises on valid cognition - Dge-vdun-grub-pa, Dalai Lama I. (Paṇ-chen bsod-nams grags-pa literature series, 2002)
Study on the commentary of seven pramāṇaśastra (Buddhist logic) by Acharya Dharmakīrti, 7th century